Shared diagnostic genes and potential mechanisms between intervertebral disc degeneration and diabetes mellitus revealed by integrated transcriptomic analysis and machine learning - Song, Bao; Wang, Jianmin; Tang, Hao; Li, Huadong; Zhang, Wanli (Frontiers in Endocrinology, 2025)
IntroductionIntervertebral disc degeneration (IDD) and diabetes mellitus (DM) are clinically associated beyond traditional risk factors, yet the shared molecular mechanisms remain unclear.MethodsWe integrated transcriptomic data from IDD and DM cohorts, performed differential expression and protein–protein interaction (PPI) network analyses, and applied machine learning to identify shared diagnostic genes. Pathway enrichment, immune infiltration analyses, and experimental qPCR validation were conducted to explore mechanisms and confirm findings.ResultsWe identified 138 shared differentially expressed genes enriched in immune-related pathways. Seven hub genes, including PRTN3, were identified by Random Forest models. PRTN3 showed consistent upregulation across discovery, validation, and internal cohorts. Pathway and immune analyses revealed strong associations between PRTN3 expression and neutrophil-related processes in both IDD and DM. Experimental validation confirmed PRTN3 upregulation in blood samples from patients with concurrent IDD and DM.DiscussionOur findings suggest that immune-inflammatory mechanisms, particularly involving neutrophils, underlie the comorbidity between IDD and DM. PRTN3 emerges as a promising shared diagnostic biomarker and potential therapeutic target for these conditions.